Interventions to Reduce Skin-related Self-stigma: A Systematic Review - Juliane Traxler; Caroline F. Z. Stuhlmann; Hans Graf; Marie Rudnik; Lukas Westphal; Rachel Sommer (Medical Journals Sweden, 2024)
Self-stigma beliefs are common among people with visible chronic skin diseases and can negatively affect their quality of life and psychosocial wellbeing. Hence, evidence-based interventions are urgently needed. The objective for this systematic review was to summarize research on available interventions and evaluate their benefits and limitations. Following PRISMA guidelines, we conducted an electronic database search of four databases (EMBASE, PsycINFO, PubMed, Web of Science). Studies were eligible if they (a) investigated interventions to reduce self-stigma in adults with chronic skin disease, (b) were original empirical articles, and (c) were written in English or German. Two independent reviewers conducted the abstract and full text screening as well as data extraction. The quality of the included studies was evaluated using the Critical Appraisal Skills Programme checklists. The initial search yielded 5811 abstracts; of which, 23 records were eligible. Studies addressed a broad range of skin conditions, and interventions ranged from social skills training, counselling and self-help to psychosocial and behavioural interventions. Overall, interventions had mostly positive effects on self-stigma and related constructs. However, the study quality was heterogeneous, and further efforts to develop, thoroughly evaluate and implement interventions tackling self-stigma in multiple skin conditions and languages are warranted.